Preoperative vitamin D deficiency is a risk factor for postoperative hypocalcemia in patients undergoing total thyroidectomy: retrospective cohort study - Carvalho, Genival Barbosa de; Giraldo, Lina Restrepo; Lira, Renan Bezerra; Macambira, Isabela Bergh Martins; Tapia, Marcel Adalid; Kohler, Hugo Fontan; Novoa, Joel Arévalo; Kowalski, Luiz Paulo (São Paulo Medical Journal, 2019)
BACKGROUND: The relationship between preoperative vitamin D deficiency and postoperative hypocal-cemia in cases of total thyroidectomy (TT) is a matter of controversy and may vary according to geograph-ical scenarios and populations. OBJECTIVE: The objective here was to evaluate whether preoperative vitamin D deficiency was associated with postoperative symptomatic hypocalcemia in a population in South America. DESIGN AND SETTING: Retrospective cohort study on data from all patients undergoing total thyroidec-tomy, with or without central compartment lymph node dissection, from January 2014 to December 2017, at the A. C. Camargo Cancer Center. METHODS: Patients with benign thyroid disease (Graves’ disease, multinodular goiter or hyperthyroidism) or thyroid cancer who underwent primary total thyroidectomy with or without central compartment lymph node dissection were included. The exclusion criteria were simultaneous parathyroidectomy and conditions that could affect serum calcium levels. The data collected included patient demographics, thyroid pathology, extent of the surgical procedure and complications. Information on preoperative and postoperative calcium, parathyroid hormone (PTH) and vitamin D levels were retrieved from the medical records. RESULTS: 1,347 patients were assessed and postoperative hypocalcemia was diagnosed in 284 patients (21%). The vitamin D levels were considered deficient in 243 patients (18%). Postoperative hypocalcemia was diagnosed in 357 patients (31.5%). Multivariate analysis showed that central compartment dissection and preoperative total calcium and deficient vitamin D levels were significant risk factors for postoperative hypocalcemia. CONCLUSION: Deficient preoperative vitamin D levels were a significant risk factor for postoperative hy-pocalcemia. Preoperative oral supplementation should be considered, to minimize this risk.